Determination of Cooling Load for a Solar Cooled Building in Khartoum Using a Simulation Method (University of Khartoum Engineering Journal, 2022)
Cooling load calculations are normally carried out assuming steady state conditions. This is a simple but conservative approach that leads to overestimation of the cooling capacity. For more accurate estimation of cooling loads, one has to take into account the thermal capacity of the walls and internal heat sources, which makes the problem more complicated. In this paper, the unsteady state heat transfer formulation has been used to determine the air conditioning cooling load for a building in Khartoum for a hot summer day. An explicit method was used to calculate the nodal temperatures at each time step of the thermal network. A simulation program was developed to calculate the cooling load at each time step. The building is cooled by absorption cooling system comprised mainly of an evacuated tube solar collector, a lithium bromide –water absorption air conditioner, a storage tank fitted with an auxiliary heater. A mathematical model is built to simulate the absorption cooling system for the solar cooled building and the results showed that the absorption system driven by solar energy from the evacuated tubes solar collector is enough to cover the cooling load demand by the building more than ten hours.
Keywords: Transient; Numerical; Explicit; Cooling Load; Simulation; Solar Cooling.